Research on Bearing Capacitance Distribution of Electric Vehicle Driving Motor under Random Vibration - ZHU Xianhui; SHI Nan; WANG Shuwen; LIU Yao; LIU Yuanyi; L Jianye (Journal of Harbin University of Science and Technology)
To reveal the influence of random vibration excited by road roughness on the driving motor bearing capacitance of electric vehicle, a quartervibration model of electric vehicle was established The body vibration under different grade road surface was equivalent to the bearing load The effect of equivalent load on Hertzian contact area and oil film thickness of driving motor bearing was analyzed The variation trend of the bearing capacitance of driving motor drive motor under different road grades was discussed The normal distribution results of the bearing capacitance of the driving motor was given when the electric vehicle was running under the driving cycle The simulation and experimental results showed that considering the effect of equivalent load caused by random vibration on the bearing capacitance of electric vehicle driving motor, the variation law of shaft capacitance can be more accurately described